2018
DOI: 10.1007/s13201-018-0701-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing TOC and COD removal for the biodiesel wastewater by electrocoagulation

Abstract: In this study, the chemical oxygen demand (COD) and the total organic carbon content (TOC) in biodiesel wastewater iron and aluminum electrodes arranged in a bipolar position. In the EC of the biodiesel wastewater, the effects of the supporting electrolyte, initial pH, electrolysis time and current density were examined. The results showed that the majority of the pollutants in the biodiesel wastewater were effectively removed when the iron or aluminum electrodes were used as a sacrificial anode. The highest C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…After approximately 40 min, the HA removal rate was approximately 95% for all samples, except for those with NaCl concentration of 0.5 g/L. This phenomenon can be explained by the higher ion concentration in the solution, which significantly increases the conductivity, thereby significantly improving the transfer rate of electrons on the electrode surface (Tanattı et al 2018). Correspondingly, the dissolution rate of the anode also increases, as well the amount of aluminum flocculant.…”
Section: Ha Removalmentioning
confidence: 83%
“…After approximately 40 min, the HA removal rate was approximately 95% for all samples, except for those with NaCl concentration of 0.5 g/L. This phenomenon can be explained by the higher ion concentration in the solution, which significantly increases the conductivity, thereby significantly improving the transfer rate of electrons on the electrode surface (Tanattı et al 2018). Correspondingly, the dissolution rate of the anode also increases, as well the amount of aluminum flocculant.…”
Section: Ha Removalmentioning
confidence: 83%
“…Our findings are in good concordance with those reported by Tak et al [39] who confirmed that an increase of electrolysis time from 10 to 20 min resulted in an increase of COD removal rate from 84 to 88.5% and optimal efficiency of 93.2% was achieved during 30 min. Another study [43] showed that the removal efficiency of COD increased from 59.72 to 91.32% in the interval time of 0.5-5 min and the optimum electrolysis time was found to be only 1 min. It is important to underline that the electrolysis time obtained in our study (5 min) is more economical when it is compared to other studies [37,38,40].…”
Section: Effect Of Charge Loadingmentioning
confidence: 98%
“…Because of the high pollution load of raw biodiesel wastewater and high amount of oil in water, it is difficult to treat with oxidation processes without pre-treatment. Even though high removal efficiencies have been obtained with the EC process, COD values decreased to 24,000-18,800 mg/L [41,42]. And discharge standards cannot be achieved.…”
Section: Ec Of Biodiesel Wastewatermentioning
confidence: 98%
“…The experimental system employed that was similar to ones used in our previous study [41]. EC experiments were conducted in a 250 ml bipolar batch reactor.…”
Section: Ec Of Biodiesel Wastewatermentioning
confidence: 99%